Assessing Groundwater Quality in Islamabad: A Microbiological and Physicochemical Analysis in Compliance with WHO Standards for Potable Water - Jabeen, Sadia; Ahmed, Niaz; Arshad, Muhammad; Ali, Abid; Parkash, Om (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
The study was conducted in Islamabad, Pakistan, aimed to evaluate the microbiological and physicochemical quality of potable water from various sites. Sampling was conducted in spring 2023 across 20 sites in Islamabad, selection was based on population density and proximity to potential contamination sources (urban runoff, agriculture. Microbiological parameters (total coliforms, fecal coliforms, and E. coli using the Most Probable Number (MPN) method and physicochemical parameters such as pH, electrical conductivity (EC), total dissolved salts (TDS), turbidity, hardness, chloride, and nitrate were measured using standard procedures. The findings highlighted significant disparities in E. coli contamination across different sites, with the highest count at Site H (21.8) and the absence of E. coli at multiple sites (A, E, G, K, and N), indicating a need for site-specific microbial monitoring. Physicochemical analysis revealed variability in water quality, with pH levels ranging from slightly acidic to slightly alkaline. Notably, turbidity levels were highest at Sites D1 measuring a 93.5 Nephelometric Turbidity Unit (NTU), while Site F exhibited the highest EC (4020 µS) and TDS (3015 mg/L). High EC, turbidity and TDS at these specific sites were attributed to geological mineral dissolution, agricultural runoff, and inadequate sewage management. Site H recorded the highest nitrate concentration at 20 mg/L, suggesting contamination from agricultural runoffs or sewage. The study underscores the importance of continuous monitoring and tailored interventions to ensure safe drinking water standards across different locations and mitigate public health risks associated with contaminated groundwater.